2022
DOI: 10.3390/plants11202782
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins Increase Triterpene Production in Solanum lycopersicum Cell Cultures by Activating Biosynthetic Genes

Abstract: In this work, Solanum lycopersicum cv. Micro-Tom suspension-cultured cells were used to analyze the effect of different elicitors including β-cyclodextrins (CD), methyl jasmonate (MJ), β-glucan (Glu) and 3-hexenol (Hex) separately and the combined treatments of CD + MJ, CD + glu and CD + Hex on triterpene compound production after 24, 72 and 96 h. Moreover, we studied the changes induced by elicitors in the expression of key biosynthetic genes to elucidate the regulation of the triterpene biosynthetic pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…In contrast, treatment with β-CD 0.005 mol dm −3 resulted in an increase in cell weight, indicating a stimulatory effect. Previous studies have shown that CD can enhance the production of secondary metabolites, namely terpenes, in Solanum lycopersicum (tomato) culture cells, supporting these findings [44]. In fact, CD molecules have been used to encapsulate specific plant growth regulators, such as cytokinins [45].…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, treatment with β-CD 0.005 mol dm −3 resulted in an increase in cell weight, indicating a stimulatory effect. Previous studies have shown that CD can enhance the production of secondary metabolites, namely terpenes, in Solanum lycopersicum (tomato) culture cells, supporting these findings [44]. In fact, CD molecules have been used to encapsulate specific plant growth regulators, such as cytokinins [45].…”
Section: Discussionmentioning
confidence: 58%